2020
DOI: 10.3390/microorganisms8101623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Debaryomyces hansenii and Lactobacillus buchneri Starter Culture on Aspergillus westerdijkiae Ochratoxin A Production and Growth during the Manufacture of Short Seasoned Dry-Cured Ham

Abstract: Recently, specific dry-cured hams have started to be produced in San Daniele and Parma areas. The ingredients are similar to protected denomination of origin (PDO) produced in San Daniele or Parma areas, and include pork leg, coming from pigs bred in the Italian peninsula, salt and spices. However, these specific new products cannot be marked as a PDO, either San Daniele or Parma dry cured ham, because they are seasoned for 6 months, and the mark PDO is given only to products seasoned over 13 months. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
(147 reference statements)
0
14
0
Order By: Relevance
“…Additionally, a decrease in OTA production and accumulation in food due to the presence of D. hansenii has been reported [ 90 , 91 , 95 , 100 ]. Very recently, the effect of D. hansenii on A. westerdijkiae ochratoxin A production and growth has been also described [ 101 ], however, it is important to mention that when a starter culture containing bacteria plus D. hansenii was co-inoculated with A. westerdijkiae or P. nordicum in meat-based media, OTA production was stimulated indicating possible unforeseen safety problems [ 102 ]. These findings are an important wake-up call regarding the need for specific studies in each case and, in fact, very recently new information indicating that D. hansenii reduced the OTA levels produced by P. nordicum in dry-meat products has been provided [ 99 ].…”
Section: Other Debaryomyces Hansenii Functions Beyond Just Improving Overall Characteristics Of Sausages and Dry-meat mentioning
confidence: 99%
“…Additionally, a decrease in OTA production and accumulation in food due to the presence of D. hansenii has been reported [ 90 , 91 , 95 , 100 ]. Very recently, the effect of D. hansenii on A. westerdijkiae ochratoxin A production and growth has been also described [ 101 ], however, it is important to mention that when a starter culture containing bacteria plus D. hansenii was co-inoculated with A. westerdijkiae or P. nordicum in meat-based media, OTA production was stimulated indicating possible unforeseen safety problems [ 102 ]. These findings are an important wake-up call regarding the need for specific studies in each case and, in fact, very recently new information indicating that D. hansenii reduced the OTA levels produced by P. nordicum in dry-meat products has been provided [ 99 ].…”
Section: Other Debaryomyces Hansenii Functions Beyond Just Improving Overall Characteristics Of Sausages and Dry-meat mentioning
confidence: 99%
“…[80]. The occurrence of A. westerdijkiae has already been described in various meat products in many countries worldwide [30,[81][82][83], and its growth was associated with the presence of the OTA toxin in dry-cured meat products [84][85][86]. A. ochraceus was detected in OTA-contaminated sausages [75] or dry cured ham [27,76].…”
Section: Production Of Ota In Meat and Meat Productsmentioning
confidence: 96%
“…The biopreservation ability of different LAB strains on coffee, fruits, and vegetables has been demonstrated [ 72 , 73 , 74 ]. Only Iacumin et al [ 75 ] reported Lactobacillus buchneri and D. hansenii as potential biological preservatives that could be used to inhibit OTA production by A. westerdijkiae in dry-cured hams. Nevertheless, there is a lack of studies on antifungal LAB against OTA in dry-cured hams.…”
Section: Biocontrol Strategiesmentioning
confidence: 99%
“…To our knowledge, only short-seasoned dry-cured hams have been evaluated for the effect of D. hansenii and L. buchneri as biological agents on the sensorial acceptability of ham. The results showed no sensorial differences between the biocontrol treatment group and the control group [ 75 ]. Iacumin et al [ 78 ] explored the inhibitory activity of yeast on OTA production during speck production, and performed a sensory analysis.…”
Section: Biocontrol Strategiesmentioning
confidence: 99%